Letter from Jane Tolmach - Jane Tolmach:::::: (1969)
A letter to Democratic State Central Committee members, Jane Tolmach announces her candidacy for State Women's Chairman. She highlights her two years of service as Chairman-South of the Women's Division and her efforts to unify party factions through cooperative projects. Noting that the chairmanship alternates to the South that year, she asks for members' votes and looks forward to the upcoming State Convention in Sacramento.